Przeobrażenia systemu zarządzania przedsiębiorstwem : Studium przypadku - Tarczydło, Beata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper presents results of a case study the Polish market carried out in. Transformations of a company management system resulting from its deep restructuring were described. The particular importance was attached to changes related to implementing the SAP R/3 system. As a result of conducted analyses and publications researched there were formulated recommendations for entrepreneurs interested in effective change management in a similar case. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 71-84